A Novel Route to Substituted 2‐(N‐Arylamino)benzothiazoles via Iron‐Promoted C‐S Bond Formation. Issue 1 (3rd January 2019) - Pinapati, Srinivasa rao; Mandapati, Usha rani; Tamminana, Ramana; Rudraraju, Ramesh raju
Abstract: The synthesis of 2‐aminobenzothiazoles has been demonstrated in the presence of transition metal under mild reaction conditions. In this paper, disubstituted thioureas have also been reported from isothiocyanates at room temperature. Subsequently, C−S cross‐coupling reaction was described for the construction of benzothiazoles using cheap, readily available and air stable Iron catalyst. Moreover, no other byproducts could be observed except target products. Furthermore, control experiments were performed for reveal the mechanism. In addition, a broad range of substrate scope has been explored. Abstract : The synthesis of 2‐aminobenzothiazoles has been demonstrated in the presence of transition metal under mild reaction conditions. In this paper, disubstituted thioureas have also been reported from isothiocyanates at room temperature. Subsequently, C‐S cross‐coupling reaction was described for the construction of benzothiazoles using cheap, readily available and air stable Iron catalyst. Moreover, no other byproducts could be observed except target products. Furthermore, control experiments were performed for reveal the mechanism. In addition, a broad range of substrate scope has been explored.